Pengaruh Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Motor Listrik Di Sentrik Bali - Anak Agung Bagus Yudistira Diputra; Ni Made Hartini (Universitas Triatma Mulya, 2024)
Electric motorcycles are a type of motorcycle that uses electrical energy as the driving force of the motorcycle. Electric motorcycles are quite popular in the current era because they can reduce air pollution so that they can support cities towards pollution-free. Electric motorcycles have entered Indonesia in 2000 and have developed with variants until now. This study aims to analyze the influence of promotion and product quality on the purchase decision of electric motorcycles in Sentrik Bali. This study uses a quantitative descriptive research method. The sample determination technique used in this study is a purposive sampling research method, by providing questionnaires to customers or consumers who have bought electric motorcycles in Sentrik Bali who are considered able to provide information according to existing facts. The analysis of this study uses multiple linear regression analysis. The results of the study show that: 1) Promotion (X1) has a positive and significant influence on the purchase decision (Y) of electric motorcycles in Sentrik Bali, 2) Product quality (X2) has a positive influence on the purchase decision (Y) of electric motorcycles in Sentrik Bali, and 3) The most dominant independent variable has a positive influence on the purchase decision (Y) of electric motorcycles in Sentrik Bali, namely product quality (X2)